(untitled) (Semiárida, 2020)
In La Rioja plains, roller chopping and buffelgrass seeding is a widespread strategy for forage rec uperation of deg raded rangelands. Native grass species seeding arises a s apossible alternative strategy. The purpose of this study was to evaluate the medium time impacts of roller chopping and roller chopping + native species seeding on grass forage yield, cover and density and woody cover in degraded sites of critic environments of the mentioned region. Four treatments were evaluated, T0=control, T1=Roller chopping, T2= Roller chopping+Trichloris crinite (Lag.) Parodi seeding and T3= Roller chopping+Trichloris crinite (Lag.) Parodi and Pappophorum vaginatum Phil. seeding on three degraded environments. T1, T2 y T3 produced important increments (p<0.05) on grass forage grass, total perennial grass cover and density respect to T0. Initial impacts of roller chopping with and without seeding produced 68±13% diminution of woody cover with an annual recuperation rate of 7±2%. Results of this study suggest that, especially roller chopping + native grass seeding would be a promising alternative strategy for rapid recuperation of grass forage capacity of degraded areas at La Rioja plains.